Assembly of Immunogenic Protein Particles toward Advanced Synthetic Vaccines. Issue 8 (23rd December 2022) - Chen, Shuxiong; Quan, Diana H.; Sam, Gayathri; Ozberk, Victoria; Wang, Xiaonan T.; Halfmann, Peter; Pandey, Manisha; Good, Michael F.; Kawaoka, Yoshihiro; Britton, Warwick J.; Rehm, Bernd H. A.
Abstract: Immunogenic carrier proteins such as the non‐toxic diphtheria toxin variant, cross‐reacting material 197 (CRM197), are widely used in subunit vaccine formulations to boost immunogenicity of chemically conjugated antigens. Conjugate vaccines are inherently expensive due to laborious manufacturing steps. Here, this work develops a particulate vaccine platform based on using engineered Escherichia coli to assemble CRM197‐antigen fusion proteins into discrete submicron‐sized particles. This approach enables precise loading of diverse antigens and epitopes enhancing their immunogenicity. A cost‐effective, high‐yield, and scalable biomanufacturing process is developed. Purified particulate CRM197‐antigen vaccines are ambient‐temperature stable. CRM197 particles incorporating pathogen‐specific antigens or epitopes from SARS‐CoV‐2, Streptococcus pyogenes (group A), and Mycobacterium tuberculosis induced cell‐mediated and humoral immune responses mediating protective immunity in respective animal models of infection. The CRM197 particle vaccine platform is versatile, enabling co‐delivery of selected antigens/epitopes together with immunogenic CRM197 as discrete stable particles avoiding laborious manufacture of soluble CRM197 and antigen followed by chemical conjugation. Abstract : A synthetic particulate vaccine platform is developed based on engineering Escherichia coli to assemble CRM197‐antigen fusion proteins into discrete submicron‐sized particles. This approach enables precise loading of diverse antigens and epitopes, enhancing their immunogenicity. A cost‐effective biomanufacturing process is developed. CRM197 particles are designed to induce humoral and cell‐mediated protective immunity against SARS‐CoV‐2, Streptococcus pyogenes (group A) and Mycobacterium tuberculosis .